Interaction mechanism between cereal phenolic acids and gluten protein: protein structural changes and binding mode. (27th July 2022) - Feng, Yulin; Feng, Xuejia; Liu, Shuchang; Zhang, Huijuan; Wang, Jing
Abstract: BACKGROUND: Phenolic acids are antioxidant nutrients in cereals and affect the quality of wheat products and the properties of gluten protein. Gallic acid (GA), caffeic acid (CA), syringic acid (SA), and p ‐coumaric acid ( p ‐CA) were selected to study the interaction mechanism between cereal phenolic acids and gluten protein. RESULTS: The results showed that adding GA significantly ( P  < 0.05) decreased the content of free sulfhydryl in gluten proteins by 70–87.26% compared with the control group. The aggregates' behavior of gluten protein induced by adding the phenolic acids would produce oversized particles (>5000 nm). Adding the selected phenolic acids changed the hydrogen‐bond linkage of protein secondary structure. Zeta potential values of gluten protein increased significantly ( P  < 0.05) by 14.41%, 26.49%, 30.77%, and 57.93% for CA, p ‐CA, GA, and SA respectively added at 0.03 g kg −1 . Moreover, the gluten protein surface hydrophobicity increased when the phenolic acids were added at 0.03 g kg −1, displaying the effect of the phenolic acid on the hydrophobic interaction of protein. Molecular docking results showed that the selected phenolic acids could interact with glutenin and gliadin using hydrogen‐bond formation, and SA had the strongest binding with glutenin and gliadin. CONCLUSION: The results demonstrated that the selected phenolic acids could interact with gluten protein via covalent cross‐linking as well as by hydrogen bonding, thereby changing the structure of the gluten protein. This exploration is expected to provide theoretical support for the development and utilization of whole‐grain foods. © 2022 Society of Chemical Industry.